The Influence of the Role-Play Method on the Communication Skills of Midwifery Students - Nova Hikmawati; Iit Ermawati (Universitas Nurul Jadid Paiton Probolinggo, East Java, Indonesia, 67291, 2026)
Effective communication skills are essential competencies for midwifery students in providing quality maternal and neonatal care. This study aimed to analyze the influence of the role-play method on the communication skills of midwifery students. The research employed a quantitative approach using a quasi-experimental design with a pre-test and post-test control group. A total of 60 midwifery students were selected through purposive sampling and divided into intervention (N=30) and control groups (N=30). The intervention group received communication training through role-play activities, while the control group received conventional lecture-based learning. Data were collected using a standardized communication skills assessment questionnaire and observation checklist. The results showed a significant improvement in the communication skills scores of students in the intervention group compared to the control group (p < 0.05). Role-play activities enhanced students’ confidence, empathy, active listening, and interpersonal communication abilities during simulated patient interactions. The findings indicate that the role-play method is an effective and interactive learning strategy for improving communication competencies among midwifery students. The study implies that integrating role-play into midwifery education curricula can support the development of professional communication skills needed in clinical practice.